From Blueprint to Digital Model: The Information Age, Archives and the Future of Architectural History* - Sabatino, Michelangelo (Enquiry The ARCC Journal for Architectural Research, 2008)
The digital revolution has not only transformed the process of thinking and making architecture,but has also led to shifts for researchers in the field and the institutions that safeguard and interpretevidence of the architect's design process. As the rise of PowerPoint made it less cumbersometo view multiple images simultaneously, pioneering art historian Heinrich Wöfflin's morelimited binary lantern slide presentation was effectively rendered obsolete. However, digital imagingand projection in the field brought risks as great as the new freedoms it afforded. The shiftfrom a work environment dominated until recently by drawings on paper and architectural models(even as CAD was being implemented over the last 20 years) to one dominated by digitaldesign and 3D modeling has irrevocably affected the ways contemporary architects produceand save their drawings as well as how they are stored and accessed in archives, how they aredisplayed, and how they are published. As technology has brought new horizons to the profession,the image of the architect has gone from the solitary scholar of Medieval architecture depictedby A. W. N. Pugin in 1841 to that of savvy manager overseeing large firms like Foster +Partners; the historian too has shed the image of recluse toiling in the bowels of a dusty archiveor library.1